Lycium barbarum glycopetide prolong lifespan and alleviate Parkinson’s disease in Caenorhabditis elegans - Zheng, Jingming; Luo, Zhenhuan; Chiu, Kin; Li, Yimin; Yang, Jing; Zhou, Qinghua; So, Kwok-Fai; Wan, Qin-Li (Frontiers in Aging Neuroscience, 2023)
Introduction Lycium barbarum glycopeptide (LbGp) is the main bioactive compound extracted from the traditional Chinese medicine. L. barbarum berries and has been proven to have numerous health benefits, including antioxidative, anti-inflammatory, anticancer, and cytoprotective activities. However, the antiaging effect of LbGp remains unknown. Methods The lifespan and body movement of C. elegans were used to evaluate the effect of LbGp on lifespan and health span. The thrashing assay was used to determine the role of LbGp in Parkinson’s disease. To investigate the mechanisms of LbGp-induced antiaging effects, we analyzed changes in lifespan, movement, and the expression of longevity-related genes in a series of worm mutants after LbGp treatment. Results We found that LbGp treatment prolonged the lifespan and health span of C. elegans. Mechanistically, we found that LbGp could activate the transcription factors DAF-16/FOXO, SKN-1/Nrf2, and HSF-1, as well as the nuclear receptor DAF-12, thereby upregulating longevity-related genes to achieve lifespan extension. In addition, we found that the lifespan extension induced by LbGp partially depends on mitochondrial function. Intriguingly, LbGp also ameliorated neurodegenerative diseases such as Parkinson’s disease in a DAF-16-, SKN-1-, and HSF-1-dependent manner. Conclusion Our work suggests that LbGp might be a viable candidate for the treatment and prevention of aging and age-related diseases.